SOURCES AND MECHANISMS OF FORMATION OF ALKALINE RARE-METAL GRANITES AT THE ZASHIKHINSKY MASSIF BASED ON GEOCHEMICAL AND Nd ISOTOPE DATA - N. V. Alymova; A. A. Vorontsov; S. I. Dril; I. A. Sotnikova (Геодинамика и тектонофизика, 2022)
The intraplate alkaline-granite magmatism essentially contributes to formation of rare-metal strategic raw materials. In the Major Sayan Fault of the East Sayan Mountains, the rocks of the Zashikhinsky (Pz3) massif were studied through the isotope-geochemical analysis to identify probable sources of alkaline-granite magma and mechanisms of their evolution resulting in ore accumulations, up to the formation of Nb-Ta deposits. The Nd isotopic characteristics of its alkaline granites were obtained for the first time. Together with the results of mineralogical and geochemical studies, they were applied for modeling its formation, in which crystallization differentiation of alkaline granite melts proceeds simultaneously with their assimilation of the enclosing granite-metamorphic formations.